Restrições ao direito de defesa em harmonia com os princípios constitucionais - Chiovitti, Alexandre Paulichi (2012)
The main goal of this study is to analyze the hypotheses of restrictions on the right of full defense, catalyzed both by constitutional and legal systems, but viewing it from the perspective of the confluence with the Brazilian Federal Constitution s policy. After all, the constitutional right of full defense has the stigma of a invulnerable and intangible principle of law (now erected as a legal principle, as some law-writers prefer), which should not suffer any kind of blemish or mitigation, under penalty of violating the most relevant scopes of the jurisdiction. Indeed, the constitutional right of full defense fits in the procedural law as an issue of constitutional nature, erected as an institute of fundamental importance. So the question is: could an institute with such force and scope be actually restricted? In being so, may the law limit what the Constitution classifies as a wide and ample right as that? Or it would only be possible to have such restrictions if they are effectively contained in the text of the Constitution itself? The theme of this study is justified, in our understanding, by the recognition that our legal system provides, in several legislative vehicles, assumptions limiting the right of defense. Would, after all, these exceptions be unconstitutional? Or our legal system can authorize and assimilate these very exceptions? Finally, we intend to demonstrate how these institutes interrelate with each other, guaranteeing and restricting, in some points and in some matters, the right of defense